Quantification, Monetary Valuation, and Recognition of Mangrove Blue Carbon Assets: An Environmental Accounting Study and Natural Capital Potential in Surumana Village, Donggala Regency (International Journal of Economics and Management Research, 2025)
This research aims to internalize the ecological value of Blue Carbon in the mangroves of Surumana Village, Donggala Regency, into an accounting framework based on the principles of Environmental Accounting and Carbon Economic Value (NEK). A descriptive quantitative research method was employed, utilizing Systematic Stratified Sampling (10 x 10 m plots) for field inventory. Above Ground Biomass (AGB) data were calculated using Multivariate Allometric Equations and converted into Carbon Dioxide Equivalent (CO2e) stocks using IPCC standard factors. The subsequent key stage involved Monetary Valuation of the total CO2e using a proxy price from IDX Carbon (IDR 144,000/tCO2e). Physical quantification results indicate that the total CO2e stock stored in the Surumana Mangroves (4.34 Ha) is 28,764.48 Ton CO2e, dominated by the Nypa fruticans species (71.95%). The Monetary Valuation (Fair Value) resulted in a total asset value of IDR 4,141,376,012.67. This valuation figure meets the Level 1 Input criteria in the Fair Value measurement hierarchy (PSAK 113) as it utilizes active market transaction prices.From an accounting perspective, this Blue Carbon stock fulfills the criteria for Biological Assets and is recognized as regional Natural Capital. The recognition of this IDR 4.14 billion asset is essential for supporting the preparation of the regional Natural Resource Balance Sheet (NSA) and enhancing local government accountability. Consequently, mangrove degradation can now be recorded as a measurable impairment of asset value, fostering conservation protection based on measurable economic value.